Examining the Effectiveness of a Case Management Program for Custodial Grandparent Families - Lenora Campbell; Dana L. Carthron; Margaret Shandor Miles; LaShanda Brown (Nursing Research and Practice)
Researchers have identified complex needs of custodial grandparent families and lack of access to needed resources such as housing, financial and legal assistance, and health care. Case management links these families with needed services while helping them develop skills to promote their health and well-being. This paper describes a case management program for custodial grandparent families using a nurse-social worker case management team. data were collected from 50 grandparents and 33 children using surveys and semi-structured instruments. Physical and mental health outcomes were measured using Short Form-12 Health Survey (SF 12) to measure the perceived quality of health for grandparents and the Child Behavior Checklist to measure the emotional and behavioral functioning of grandchildren. Grandparents more positively perceived their mental health after participating in the program. Perceptions about physical health were generally the same before and after the program. Grandparents' reported that many grandchildren had emotional and behavioral problems in the clinical range. These findings highlight the need for further research on the mental health needs of children being parented by grandparents as well as determining effective models and interventions to minimize adverse effects of parenting on grandparents.